Effect of bleaching agents and soft drink on titanium surface topography - Faverani, Leonardo P. [UNESP] (2014)
The effects of carbamide peroxide, hydrogen peroxide and cola soft drink on the topographic modifications of commercially-pure titanium (CP-Ti) and Ti-6Al-4V were investigated. Ti discs were divided into 18 groups (n=4) based on the solution treatment and Ti type. Specimens were immersed in 3 mL of each solution for 4 h per day (for the remaining 20 h, discs were left dry or immersed in artificial saliva) for 15 days. For control, specimens were immersed in only artificial saliva. Ti surfaces were examined using scanning electron (SEM) and atomic force (AFM) microscopes and their surface roughness (in mu m) and surface chemical modifications were investigated. Data were analyzed by ANOVA and Tukey's test (=0.05). Groups immersed in 35% hydrogen peroxide showed the highest roughness (Ra) (171.65 +/- 4.04 for CP-Ti and 145.91 +/- 14.71 for Ti-6Al-4V) (p<0.05), followed by groups treated with carbamide peroxide 16% (110.91 +/- 0.8 for CP-Ti and 49.28 +/- 0.36 for Ti-6Al-4V) and 35% (65.67 +/- 1.6 for CP-Ti and 53.87 +/- 1.98 for Ti-6Al-4V); treatment with artificial saliva did not affect the results. These values were statistically superior to those observed prior to the treatment and to those of the control group (31.0 +/- 0.99 for CP-Ti and 29.95 +/- 0.58 for Ti-6Al-4V). Cola soft drink did not alter the surface roughness of either Ti type (p>0.05). SEM and AFM revealed dramatic changes in the specimens surfaces immersed in the 35% hydrogen peroxide, mainly for CP-Ti. No detectable chemical modifications on the Ti surface were observed. Bleaching agents promoted significant changes in Ti topography, which could affect the longevity of implants treatments. (c) 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 102B: 22-30, 2014.